The Declining Deposit to Loan Ratio - What Can the Banks Do? - Sigbjørn Atle Berg (Norges Bank, 2012)
We have been exploring possible explanations for the strong decline in the ratio between bank deposits held by the non-financial sector in Norway, and the bank loans taken by the same sector. We have followed two different but related lines of reasoning. First, we have been looking at the relative return on bank deposits and on the relative costs of bank loans in a portfolio model approach. Second, we have tried to follow financial flows to identify structural changes in the Norwegian markets that could have an effect on the deposit-to-loan ratio.
hdl:11250/2507173
Keywords: 330